Students' Mathematical Reasoning Ability and Self-Efficacy Viewed from the Application of Problem Based Learning and Contextual Teaching and Learning Models Assisted - Nurlinda, Epi; Azis, Zainal; Nasution, Marah Doly (JMEA : Journal of Mathematics Education and Application, 2024)
The aim of this research is to reveal; (1) the significant influence of PBL and CTL models assisted by interactive media on students' mathematical reasoning abilities, (2) the interaction between KAM and the application of learning models on students' mathematical reasoning abilities, (3) the significant influence of the application of PBL and CTL models assisted by interactive media on self-efficacy students, (4) knowing the interaction between students' initial mathematics abilities and learning models on students' self-efficacy. Quasi experiment is applied, especially counter balanced design with instruments: (1) test of students' initial mathematical abilities, (2) test of students' mathematical reasoning abilities, (3) self-efficacy questionnaire. Infrential data uses covariance analysis (ANCOVA). The research results showed that: (1) The two experimental classes taught using the PBL (Problem Based Learning) model and the CTL (Contextual Teaching and Learning) model assisted by interactive media had a significant influence on students' mathematical reasoning abilities. (2) There is an interaction between initial mathematics abilities (KAM) and the learning model used on students' mathematical reasoning abilities. (3) The two experimental classes taught using the PBL (Problem Based Learning) model and the CTL (Contextual Teaching and Learning) model assisted by interactive media have a significant influence on student self-efficacy. (4) There is an interaction between initial mathematics abilities (KAM) and the learning model used on student self-efficacy.